Comparison of transcatheter edge-to-edge and surgical repair in patients with functional mitral regurgitation using a meta-analytic approach - Felbel, D.; Paukovitsch, M.; Förg, R.; Stephan, T.; Mayer, B.; Keßler, M.; Tadic, M.; Dahme, T.; Rottbauer, W.; Markovic, S.; Schneider, L. (Frontiers in Cardiovascular Medicine, 2023)
Background Evidence regarding favorable treatment of patients with functional mitral regurgitation (FMR) using transcatheter edge-to-edge repair (TEER) is constantly growing. However, there is only few data directly comparing TEER and surgical mitral valve repair (SMVr). Aims To compare baseline characteristics, short-term and 1-year outcomes in FMR patients undergoing mitral valve (MV) TEER or SMVr using a meta-analytic approach. Methods Systematic database search identified 1,703 studies reporting on TEER or SMVr for treatment of FMR between January 2010 and December 2020. A meta-analytic approach was used to compare outcomes from single-arm and randomized studies based on measures by means of their corresponding 95% confidence intervals (CI). Statistical significance was assumed if CIs did not overlap. A total of 21 TEER and 37 SMVr studies comprising 4,304 and 3,983 patients were included. Results Patients in the TEER cohort presented with higher age (72.0 ± 1.7 vs. 64.7 ± 4.7 years, p < 0.001), greater burden of comorbidities like hypertension (p < 0.001), atrial fibrillation (p < 0.001), lung disease (p < 0.001) and chronic renal disease (p = 0.005) as well as poorer left ventricular ejection fraction (30.9 ± 5.7 vs. 36.6 ± 5.3%, p < 0.001). In-hospital mortality was significantly lower with TEER [3% (95%-CI 0.02–0.03) vs. 5% (95%-CI 0.04–0.07)] and 1-year mortality did not differ significantly [18% (95%-CI 0.15–0.21) vs. 11% (0.07–0.18)]. NYHA [1.06 (95%-CI 0.87–1.26) vs. 1.15 (0.74–1.56)] and MR reduction [1.74 (95%-CI 1.52–1.97) vs. 2.08 (1.57–2.59)] were comparable between both cohorts. Conclusion Despite considerably higher age and comorbidity burden, in-hospital mortality was significantly lower in FMR patients treated with TEER, whereas a tendency toward increased 1-year mortality was observed in this high-risk population. In terms of functional status and MR grade reduction, comparable 1-year results were achieved.